Keharmonisan Keluarga, Konformitas Teman Sebaya dan Kenakalan Remaja - ., Winarsih; Saragih, Sahat (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2016)
This study aims to determine the relationship between family harmony andconformity peers in juvenile delinquency SMK